Yttria stabilized tetragonal zirconia ceramics: preparation, characterization and applicationspplications - Sultana, N; Bilkis, K; Azad, R; Qadir, MR; Gafur, MA; Alam, MZ (Bangladesh Journal of Scientific and Industrial Research, 2018)
In this study, yttria stabilized tetragonal zirconia (YSTZ) ceramics were prepared and were sintered at different temperatures to find out the optimum sintering temperature for their better tetragonality and mechanical properties for their application as optical ferrule. Vicker’s hardness was performed by micro hardness tester and it was found to increase with the increase of sintering temperature to a maximum value, then it was decreased with higher sintering temperature. Water absorptivity and porosity were also seen to decrease as the densities of the specimens were increased. X-ray diffraction was employed to determine crystal structure of sintered samples. Surface morphology of the sintered samples was examined through field emission scanning electron microscope. Bangladesh J. Sci. Ind. Res.53(2), 111-116, 2018